Analysis the Influence of Manpower, Material, Machine, Method, Money and Environment on the Time Performance of Implementing Cold Storage Building Projects - Nurrizky, Febrian Eka; Suroso, Agus; Amin, Mawardi (ASTONJADRO, 2024)
Cold Storage Building is a building specifically designed to maintain room temperature in very cold conditions which functions as a commodity preservation area so that it can be stored fresh for a long period of time. When constructing a Cold Storage Building, a very specialist construction process is required. Therefore, it must be carried out using a certain construction method (modular construction), using special Materials (sandwich panels), requiring several specialist subcons & a lack of experienced workers. These conditions make the challenge of building a Cold Storage Building more difficult, which can affect the time performance of the project. This research aims to analyze factors that can influence time performance in the implementation of the Cold Storage Building construction project using the Multiple Linear Regression Analysis method. Based on data analysis, the equation Y = 3.166 + 0.108 X1 + 0.208 X2 + 0.040 X3 + 0.112 X4 + 0.164 Based on the results of the Coefficient of Determination Test, simultaneously Manpower Factors (X1), Material Factors (X2), Machine Factors (X3), Method Factors (X4), Money Factors (X5) and Environment Factors (X6) have an influence contribution of 87.6 % of Time Performance (Y). Meanwhile, for the results of the most dominant factors analysis using Beta Standardized x Zero-Order, it was found that the Material Factors (X2) was the most dominant factors that could influence time performance with an influence value of 34.01%. Considerations in determining alternative solutions to improve time performance on Cold Storage Building construction projects are carried out on the most dominant factors, namely the Material Factors (X2).